Anti-inflammatory potential of 2-styrylchromones regarding their interference with arachidonic acid metabolic pathways - Gomes, Ana Sara (2009)
Cyclooxygenases (COXs) are the key enzymes in the biosynthesis of prostanoids. COX-1 is a constitutive enzyme while the expression of COX-2 is highly stimulated in the event of inflammatory processes, leading to the production of large amounts of prostaglandins (PGs), in particular PGE2 and PGI2, which are pro-inflammatory mediators. Lipoxygenases (LOXs) are enzymes that produce hydroxy acids and leukotrienes (LTs). 5-LOX metabolizes arachidonic acid to yield, among other products, LTB4, a potent chemoattractantmediator of inflammation. The aim of the present work was to evaluate the anti-inflammatory potential of 2-styrylchromones (2-SC), a chemical family of oxygen heterocyclic compounds, vinylogues of flavones (2-phenylchromones), by studying their COX-1 and COX-2 inhibitory capacity as well as their effects on the LTB4 production by stimulated human polymorphonuclear leukocytes (PMNL). Some of the tested 2-SC were able to inhibit both COX-1 activity and LTB4 production which makes them dual inhibitors of the COX and 5-LOX pathways. The most effective compounds in this study were those having structural moieties with proved antioxidant activity (30,40-catechol and 40-phenol substituted B-rings). This type of compounds may exhibit anti-inflammatory activity with a wider spectrum than that of classical non-steroidal anti-inflammatory drugs (NSAIDs) by inhibiting 5-LOX product-mediated inflammatory reactions, towards which NSAIDs are ineffective.